Risk factors associated with recurrent cholera outbreaks in Borno and Adamawa states, northeast Nigeria - Janet Cherono (2024)
This study evaluates the risk factors leading to recurrent cholera outbreaks in Borno and Adamawa states, northeast Nigeria. The study focusses mainly on the two states most affected by the ongoing conflict, resulting to massive displacement of populations internally. The literature review and the methodology adopted for this study included review of existing secondary data relevant to the study area. The documents reviewed included materials such as journals, research papers, textbooks, published reports, articles, government press releases and publication on the activities of International Nongovernmental Organization. Materials were sourced through credible sites such as google scholar, research gate and the Loughborough university repository. Where relevant, data obtained from other similar contexts was used to corroborate the findings and draw conclusions. The study findings revealed that deficiency in water and sanitation infrastructure, congestion, displacement, rapid urbanization, the negative beliefs and practices, unclear guidelines on cholera control and prevention, the lack of knowledge on proper handwashing, environmental natural and man-made hazards amongst other factors contributing to cholera outbreaks. The lack of primary data posed as a major limitation to this study. Future social researchers can benefit more through collection of primary data to build on the findings and recommendations for this study. The study concludes with recommendations specific to the different players contributing to the cholera prevention and control strategies in the study locations. Further studies should be conducted to establish further to fill the knowledge gaps.